Assessment of the Implementation of Economics Curriculum and Students’ Learning Achievement in Public High Schools in Osun State, Nigeria - Adio, Y. O.; Oluwatosin, Wuraola L.; Olatunde, F. A. (NIU Journal of Social Sciences, 2021)
This paper assessed the implementation of Economics curriculum and students’ learning achievement in public high schools in Osun State, Nigeria. The study adopted two theories: constructivism learning theory and Context, Input, Process and Product (CIPP) theory. Four research questions were raised in the study; and four research hypotheses guided the study. Descriptive research design was adopted and the population for the study was all high schools in Osun State. The sample size for this study was one hundred and sixty (160) participants comprising forty (40) Economics teachers, and one hundred and twenty (120) students selected randomly from eighty-four high schools in the State. The research instruments used for data collection in this study were researcher-designed questionnaires, and Economics Students’ Achievement Test. Simple percentage, mean and standard deviation were used to analyse the research questions, while the research hypotheses were tested using Pearson Product Moment Correlation Coefficient and One-Way ANOVA at 0.05 level of significance. The findings revealed that the teaching methods mostly used by the Economics teachers for the implementation of Economics curriculum contents in High Schools include: discussion method, question and answer method, problem solving method, project method, role play method, and demonstration method.  Economics teachers utilize teaching resources for the implementation of Economics curriculum in High Schools to a medium extent. Students’ perception on the objectives of Senior Secondary School Economics curriculum was good. There is significant relationship between students’ perception of Economics curriculum objectives and learning achievement in Economics; and implementation of Economics curriculum has significant effect on students’ learning achievement in High Schools in Osun State, Nigeria. Based on these findings, recommendations were made among others that teachers should utilize the available resources for the implementation of Economics curriculum; principals in all senior secondary schools should embark on regular supervision of delivery of Economics instructions in the classroom to ensure that the appropriate methods and materials are used by the teachers; and Economics teachers should always utilize students-centred methods for the implementation of Economics Curriculum. Key words : Curriculum Implementation, Economics Curriculum, Implementation, Students’ Learning Achievement, Teaching Facilities/Resources